How to Integrate Suppliers into the Innovation Process? An Explorative Case of Champion Formalization in the Purchasing Department in Times of Open Innovation - Maier, Maximilian A.; Rück, Peter; Brem, Alexander (International Journal of Innovation and Technology Management, 2017)
Literature on the champion theory proposes the informal character of the champion’s role and also notes difficulties in institutionalizing it. Nevertheless, formally institutionalized roles that seem to fit the description of a champion can be recognized in organizations, especially as enablers of open innovation activities. However, research cannot answer how this institutionalization occurs and which factors influence it. To answer these questions, we investigate a unique single case in which a champion role was institutionalized in the purchasing department of a multinational company. The new role’s task is to identify, select, and integrate supplier innovations. Our results indicate that the informal role of the champion can be successfully institutionalized when certain success factors are considered, which are management commitment, use of success stories, and matching of champions with research and development teams. We contribute to innovation management literature by using the well-established champion theory to explain how and why large multinational companies formally establish the role of the innovation champion. Our research offers pathways for further research about both, the antecedents and the consequences of role formalization. Practitioners can build on the success factors derived in this study when formally implementing innovation champions as enablers of open innovation activitie
Keywords: New product development; innovation management; R&D management; early supplier involvement; supplier innovation; champion model; open innovation; purchasing department; buying innovations; success factors